Keratoacanthoma versus invasive squamous cell carcinoma: a comparison of dermatoscopic vascular features in 510 cases - John H. Pyne; Graham Windrum; Devendra Sapkota; Jian Cheng Wong (Mattioli1885, 2014)
Introduction: Keratoacanthoma (KA) and invasive squamous cell carcinoma (SCC) are keratinocytic tumors displaying vascular features, imaged using dermatoscopy. Objective: Compare the dermatoscopy vascular features of KA to SCC. Methods: This prospective study examined consecutive cases of 100 KA and 410 invasive SCC in a single private practice in Sydney, Australia. Vascular features were recorded in vivo direct from  patients using a non-polarized Delta 20 Heine dermatoscope. These vascular features were: linear, branching, serpentine, hairpin, glomerular and dot vessels, the presence or absence of large diameter tumor vessels, vessel presence in central verses peripheral tumor areas and tumor pink areas in different proportions. Following full excision, all cases were submitted for histopathologic diagnosis. Results: Branching vessels were the only vessel morphology that varied, with a significant incidence in KA (25.0%), compared to SCC (10.7%), P < 0.01. Large vessels were identified in 20.0% of KA, compared to 12.4% in SCC, P = 0.05. No vessels were observed in the central tumor areas in 43.4 % of KA compared to 58.0% of SCC, P = 0.01. Other data comparing the central versus peripheral tumor areas for vessels present did not reveal any distinctive associations. There were no significant differences between KA and SCC when reviewing the selected proportions of pink within the tumor. Limitations: The vascular features may be confounded by tumor depth in KA. Polarized dermatoscopy may not produce the same findings. Conclusion: This study found branching vessels to have a higher incidence in KA compared to invasive SCC. Although not statistically significant, large diameter vessels were also more frequent in KA. Proportions of pink within the tumor or central verses peripheral tumor vessel distribution were not useful diagnostic features separating KA from SCC using dermatoscopy.